Mutual occlusion between real and virtual elements in Augmented Reality based on fiducial markers - Sanches, Silvio R.R.; Tokunaga, Daniel M.; Silva, Valdinei F.; Sementille, Antonio Carlos [UNESP]; Tori, Romero (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Augmented Reality (AR) systems which use optical tracking with fiducial marker for registration have had an important role in popularizing this technology, since only a personal computer with a conventional webcam is required. However, in most these applications, the virtual elements are shown only in the foreground a real element does not occlude a virtual one. The method presented enables AR environments based on fiducial markers to support mutual occlusion between a real element and many virtual ones, according to the elements position (depth) in the environment. © 2012 IEEE.
Keywords: Augmented reality systems; Fiducial marker; Optical tracking; Virtual elements; Augmented reality; Personal computers; Computer vision